Pelatihan Manajemen Laktasi untuk Ibu Hamil dan Ibu Menyusui: Upaya Optimalisasi Tumbuh Kembang Anak - Qodri Santosa; Miko Ferrine; Muhammad Fakih; Alfi Muntafiah (Jurnal Pengabdian Pada Masyarakat, 2019)
LACTATION MANAGEMENT TRAINING FOR PREGNANT WOMEN AND BREASTFEEDING MOTHERS: EFFORTS TO OPTIMIZE CHILD GROWTH. The key person for making quality generation lies on mother, through breast milk. Breastfeeding, besides providing the best nutrition for optimal baby growth and development, it is also a form of love to a baby. Ironically, not all mothers realize and many mothers do not breastfeed their babies exclusively. The low level of knowledge and working mothers is often an obstacle for mothers to give exclusive breastfeeding. In Indonesia, almost 9 of 10 mothers give breast milk, but only 49.8% give exclusive breastfeeding for 6 months. Lactation management health promotion activities are carried out in accordance with WHO recommendations and the Indonesian government in promoting breastfeeding, especially increasing the achievement of the rate of early breastfeeding initiation and exclusive breastfeeding. The activities carried out using several methods: counseling, demonstration, video and discussion. We found that 54.1% of participants gave exclusive breastfeeding for 6 months, 27% for 4 months, and others 2-3 months. Wilcoxon Rank Test showed a significant difference (p = 0,000) between the score of pre-test and post-test, with a mean pre-test of 49.02 ± 19.74, and a mean post-test of 68.53 ± 20.00. Conclution: This activity increased participants' knowledge regarding lactation management.